Aspectos do controle de resíduos de avermectinas no abate de bovinos - Prata, Camila Barbieri [UNESP] (2014)
Changes in international food controls aiming their safety occurred with the change of the century, based on the Risk Analysis and Hazard Analysis and Critical Control Points. For chemical residues, although a pre-existing problem, the situation only gained notoriety after 2010, with the presence of avermectin residues in Brazilian meat products exported to the United States and European Union. Since then, several mitigation measures were incorporated in the routine set of self-controls the processing companies.This work aimed to verify the practicality and effectiveness of these measures for effective control of processes, segregating slaughtered animals that could contribute to unacceptable levels of risk, based on monitoring of avermectins residues in two sample matrices, liver and muscle of cattle slaughtered. For the muscle matrix were analyzed 81,565 batches of animals, with 1,153 or 1.41% batches whose residues were above the avermectin MRL (Maximum Residue Level) of 10μg/kg during the years 2010 and 2011. from 2012 was used the liver matrix , with 77,056 samples being analyzed. Of these, 29,267 or 37.98% were positive for residues, with 4,602 or 5.97% above the MRL of 100μg/kg. The analytical results shown so far, the aggravation of problems at the primary link of the production chain of Brazilian beef